Investigations of thermal plasma of electric arc discharge between composite Ag–C electrodes - Veklich, A.N.; Fesenko, S.O.; Kleshich, M.M.; Boretskij, V.F.; Cressault, Y.; Teulet, Ph. (Вопросы атомной науки и техники, 2016)
The complex investigation of the arc discharge plasma between composite Ag–C electrodes in the range of 3.5 A…30 A currents was carried out. Plasma temperature in assumption of local thermodynamic equilibrium was obtained by optical emission spectroscopy. Electron densities were obtained from half-width of Ag I 466.8 nm spectral line in the assumption of dominating quadratic Stark effect emitted by plasma at arc current 30 A. Electrical conductivity and electron density in arc discharge plasma at current 3.5 A were obtained by solution of the energy balance equation. The results of investigations of plasma arc discharge between Ag–C electrodes were compared with parameters of discharge plasma between C–Cu electrodes at arc current 3.5 A.